Impact of lowering pulmonary vascular resistance on right and left ventricular deformation in pulmonary arterial hypertension. (4th November 2014) - Querejeta Roca, Gabriela; Campbell, Patricia; Claggett, Brian; Vazir, Ali; Quinn, Debbie; Solomon, Scott D.; Shah, Amil M.
<x xml:space="preserve">Abstract</x> Aims As pulmonary arterial hypertension (PAH) is associated with significant morbidity and mortality, particularly among patients with right ventricular (RV) dysfunction, we aimed to determine the impact of therapy to reduce pulmonary vascular resistance (PVR) on RV and LV deformation in PAH. Methods and results Right ventricular free wall longitudinal strain (FWLS) and LV global circumferential strain (CS) were measured at baseline, 12 weeks, and 24 weeks in 68 patients with advanced PAH randomized to imatinib or placebo in the Imatinib in Pulmonary arterial hypertension, a Randomized Efficacy Study (IMPRES) trial, and compared with 30 healthy controls. Compared with controls, PAH was associated with impaired RV FWLS (–15.9 ± 5.4 vs. –30.8 ± 4.3, respectively; P < 0.0001) and LV septal CS (–24.2 ± 8.2 vs. –31.4 ± 5.3, respectively, P < 0.0001), but not LV global CS. Improvement in PVR and mean pulmonary artery pressure (MPAP) over a 24‐week period was significantly associated with improvement in RV FWLS (r = 0.39, P = 0.02; 0.33, P = 0.04 respectively), LV global CS (r = 0.61, P = 0.0001; r = 0.60, P = 0.0001, respectively), and LV septal CS (r = 0.50, P = 0.005; r = 0.56, P = 0.002, respectively). These associations were most robust with LV global and septal CS. Imatinib therapy was associated with improvement in RV FWLS compared with placebo. Conclusions PAH is associated with impaired biventricular deformation. Reduction in PVR is associated with improvements in both RV and LV deformation, coupled to improvements in MPAP and stroke volume index, with LV global and septal CS the strongest correlates of these changes. RV FWLS is sensitive to treatment effect, demonstrating greater improvement with imatinib compared with placebo. Trial registration: NCT00902174